Exposure to an enriched CO 2 atmosphere alters carbon assimilation and allocation in a pine forest ecosystem - Karina V. R. Schäfer; Ram Oren; David S. Ellsworth; Chun‐Ta Lai; Jeffrey D. Herrick; Adrien C. Finzi; Daniel D. Richter; Gabriel G. Katul (Global Change Biology, 2003)
We linked a leaf‐level CO 2 assimilation model with a model that accounts for light attenuation in the canopy and measurements of sap‐flux‐based canopy conductance into a new canopy conductance‐constrained carbon assimilation (4C‐A) model. We estimated canopy CO 2 uptake ( A nC ) at the Duke Forest free‐air CO 2 enrichment (FACE) study. Rates of A nC estimated from the 4C‐A model agreed well with leaf gas exchange measurements ( A net ) in both CO 2 treatments. Under ambient conditions, monthly sums of net CO 2 uptake by the canopy ( A nC ) were 13% higher than estimates based on eddy‐covariance and chamber measurements. Annual estimates of A nC were only 3% higher than carbon (C) accumulations and losses estimated from ground‐based measurements for the entire stand. The C budget for the Pinus taeda component was well constrained (within 1% of ground‐based measurements). Although the closure of the C budget for the broadleaf species was poorer (within 20%), these species are a minor component of the forest. Under elevated CO 2 , the C used annually for growth, turnover, and respiration balanced only 80% of the A nC . Of the extra 700 g C m −2 a −1 (1999 and 2000 average), 86% is attributable to surface soil CO 2 efflux. This suggests that the production and turnover of fine roots was underestimated or that mycorrhizae and rhizodeposition became an increasingly important component of the C balance. Under elevated CO 2 , net ecosystem production increased by 272 g C m −2 a −1 : 44% greater than under ambient CO 2 . The majority (87%) of this C was sequestered in a moderately long‐term C pool in wood, with the remainder in the forest floor–soil subsystem.

Reduction of forest floor respiration by fertilization on both carbon dioxide‐enriched and reference 17‐year‐old loblolly pine stands - JOHN R. BUTNOR; KURT H. JOHNSEN; RAM OREN; GABRIEL G. KATUL (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (CO 2 e ) increases soil respiration rates in forest, grassland, agricultural and wetland systems as a result of increased growth, root biomass and enhanced biological activity of soil microorganisms. Less is known about how forest floor fluxes respond to the combined effects of elevated CO 2 and nutrient amendments; until now no experiments have been in place with large forest trees to allow even preliminary investigations. We investigated changes in forest floor respiration (S ff ) in a Pinus taeda L. plantation fumigated with CO 2 by using free‐air CO 2 enrichment (FACE) technology and given nutrient amendments. The prototype FACE apparatus (FACEp; 707 m 2 ) was constructed in 1993, 10 years after planting, on a moderate fertility site in Duke Forest, North Carolina, USA, enriching the stand to 55 Pa (CO 2 e ). A nearby ambient CO 2 (CO 2 a ) plot (117 m 2 ) was designated at the inception of the study as a reference (Ref). Both FACEp and Ref plot were divided in half and urea fertilizer was applied to one half at an annual rate of 11.2 g N m −2 in the spring of 1998, 1999 and 2000. Forest floor respiration was monitored continuously for 220 days – March through November 2000 – by using two Automated Carbon Efflux Systems. Thirty locations (491 cm 2 each) were sampled in both FACEp and Ref, about half in each fertility treatment. Forest floor respiration was strongly correlated with soil temperature at 5 cm. Rates of S ff were greater in CO 2 e relative to CO 2 a (an enhancement of ∼178 g C m −2 ) during the measurement period. Application of fertilizer resulted in a statistically significant depression of respiration rates in both the CO 2 a and CO 2 e plots (a reduction of ∼186 g C m −2 ). The results suggest that closed canopy forests on moderate fertility sites cycle back to the atmosphere more assimilated carbon (C) than similar forests on sites of high fertility. We recognize the limitations of this non‐replicated study, but its clear results offer strong testable hypotheses for future research in this important area.